Predicting software analysis process risks using linear stepwise discriminant analysis : Statistical methods - Elzamly, Abdelrafe; Hussin, Burairah; Abu Naser, Samy S.; Doheir, Mohamed A. S. (IJAIST, 2015)
The aim of this work is to introduce the linear stepwise discriminant analysis model to predict software risks in software analysis development process. These methods were used to measure and predict risks by using control techniques. Furthermore, we predict risks to three levels (high, medium, low). In addition, these risk control techniques were used to mitigate and predict risk model in software analysis development process looking at Table 31.